1996
DOI: 10.1016/0014-5793(96)00845-9
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer's presenilin 1 gene expression in platelets and megakaryocytes

Abstract: The presenilin 1 (PSI) gene located on chromosome 14 has been linked with the majority of early-onset FAD. The normal biological role of PS1 as well as the mechanism by which mutations in PSI cause FAD remains unknown. PSI expression in platelets and the Dami megakaryocytic cell line was examined by Western blot analysis and RT-PCR. Using an anti-Nterminus PS1 antibody we detected PSI immunoreactive bands of 44, 32 and 27 kDa in both cell types. After RT-PCR we observed that platelets and megakaryocytes carry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
2
7
0
1
Order By: Relevance
“…In order to show that platelets contain enzymes included in APP processing, we examined whether BACE-1 and presenilin-1 are present in platelets by means of Western blotting. We found that platelets contain BACE-1 and that presenilin-1 is present in platelets, in accordance with recent studies [23,24] (fig. 3).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In order to show that platelets contain enzymes included in APP processing, we examined whether BACE-1 and presenilin-1 are present in platelets by means of Western blotting. We found that platelets contain BACE-1 and that presenilin-1 is present in platelets, in accordance with recent studies [23,24] (fig. 3).…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, there are also studies suggesting that platelets are the general source of ·-sAPP and Aß 40 in human blood [20][21][22], thus either platelets or megakaryocytes may contain the whole repertoire of enzymes required for APP processing. Recently, presenilin-1 and presenilin-2 have been found to be expressed in the cells [23,24]. However, due to the low concentration of Aß 42 in plasma, the peripheral source of Aß 42 remains to be established.…”
Section: Introductionmentioning
confidence: 99%
“…In other words we demonstrate a distinction in VRSQ+ expression between brain and peripheral tissue. The PS-1 gene has several splicing variants which differ from tissue to tissue (Vidal et at., 1996;Rogaev et al, 1997). Further examination of other alternative splicing products is necessary in peripheral tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Psen1 −/− ; Psen2 −/− DKO MEF cells were transiently co-transfected with empty pcDNA3.1 or pcDNA3.1-apoER2-ΔEX5 and pcDNA3.1-PS1 WT or L282V [identical mutation to L286V but in the context of a shorter splice variant (Vidal et al, 1996)] with Lipofectamine 2000 (Invitrogen). At 24 h after transfection, cells were washed with PBS and treated with 50 μM DAPT and/or 10 nM Reelin in serum-free medium for 16 h. Cells were then harvested with SDS lysis buffer as above.…”
Section: Methodsmentioning
confidence: 99%